Perbedaan Depresi Siswa Kelas XII SMA Al Islam 1 Surakarta yang Tinggal di Asrama Binaan dan Orang Tua Kandung - Inayati MS, Annisa; Susilohati, Mardiatmi; Wicaksono, Bagus (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Depression is a mood state or mood decline, marked by distress, decreased functional activity, moodiness, and loss of interest in all or a range of activities . During its development, a teenager is vulnerable with an identity crisis and depression. Being neighborhoods far away from parents spur the onset of depression. This study aims to find out the depression rate between among high school students of class XII SMA Al Islam 1 Surakarta who live in dormitories and live with their biological parent. Methods: The study was an analytical observational research using cross sectional approach implemented in Agustus 2013 in SMA Al Islam 1 Surakarta. The sample was taken using total sampling for the entire class XII. Purposive random sampling conducted for the dormitory student that can represent the whole dormitory students and performed simple random sampling for students who live with their own biological parents according to the number of samples required (sample of dormitory students). The samples filled in ( 1 ) Curriculum vitae form, (2) L - MMPI questionnaire to find out the respondentâs truthfulness in completing the questionnaire, ( 3) BDI questionnaire to assess depression score, score â¤ 9 means no depression and score > 9 means depression. Data obtained 72 students as the subject of research and the data were foanalyzed using Chi Square test through SPSS 17.00 for Windows . Results: This research showed the Chi Square (X2) value is 0,084, while the price of X2 table on db = 1 at the 0.05 significance level is 3.481. This means that the X2 count < X2 table. In addition the p-value calculated is 0.772 or p > 0.05, then the null hypothesis is accepted. Chi-square test resultâs showed that there was no significant difference of depression level between students living in dormitories and students living with their biological parents. Conclusion: There was no difference of depression level among class XII students who live in dormitories and who live with their biological parents in SMA Al Islam 1 Surakarta. Thus the residence does not affect a students pattern of depression. Key words : depression, housing, dormitories, boarding, biological parents. Â